Comparative institutional law and economics: reclaiming economics for socio-legal research. Issue 3 (June 2019) - Gramcheva, Lyubomira
Law and economics is a controversial method of legal research, increasingly popular among some legal scholars but disliked by many others. The author discusses some of the objections raised by lawyers (as well as some economists) and argues that most of these are caused by the employment of the wrong economics on the respective side of the conjoined field. She contrasts neoclassical economics, made extremely popular by the Chicago school and Professor Richard Posner in particular, with New Institutional Economics and argues that the latter can overcome the difficulties presented by the former. While neoclassical economics seems to introduce additional problems to legal scholarship, New Institutional Economics neatly matches law's own methodological tenets. However, the analysis will remain incomplete unless a third element is added to the mix: comparative law. Thus, the author calls for the development of Comparative Institutional Law and Economics, which provides an improved explanatory methodology.